Nilai Peak Ground Acceleration di Kecamatan Prambanan, Kabupaten Sleman - Adelia Saras Nugraheni (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The 2006 Yogyakarta earthquake, with a magnitude of 6.3 Mw, caused severe structural damage and significant casualties, highlighting the high seismic vulnerability in the Special Region of Yogyakarta (DIY). Tectonic activity in this region is strongly influenced by the subduction of the Indo-Australian Plate beneath the Eurasian Plate and the presence of active faults, particularly the Opak Fault. Local geological conditions dominated by young volcanic deposits and unconsolidated alluvial sediments further enhance seismic wave amplification. This study aims to estimate the Peak Ground Acceleration (PGA) in Prambanan District using the empirical McGuire (1977) attenuation relationship based on parameters from the 2006 earthquake. Analysis was conducted on 113 observation points to map the spatial distribution of ground acceleration. The results indicate that PGA values range from 29.2 to 35.6 gal, with the highest values concentrated in the southern and southeastern parts of Prambanan, characterized by alluvial deposits of the Opak River. In contrast, lower PGA values occur in the northern area underlain by more consolidated young volcanic materials. These findings emphasize the significant influence of lithology and geomorphology on local site response to seismic shaking. The results provide an important basis for seismic hazard assessment and mitigation planning in Prambanan and surrounding areas.